Observation of early ZIF-8 crystallization stages with X-ray absorption spectroscopy. Issue 2 (15th December 2020) - Buzanich, Ana Guilherme; Kulow, Anicó; Kabelitz, Anke; Grunewald, Christian; Seidel, Robert; Chapartegui-Arias, Ander; Radtke, Martin; Reinholz, Uwe; Emmerling, Franziska; Beyer, Sebastian
Abstract : The present study investigates structural evolution of early ZIF-8 crystallization up to 5 minutes post mixing of precursor solutions using Dispersive X-ray Absorption Spectroscopy (DXAS). Abstract : The present study investigates early stages of ZIF-8 crystallization up to 5 minutes post mixing of precursor solutions. Dispersive X-ray Absorption Spectroscopy (DXAS) provides a refined understanding of the evolution of the coordination environment during ZIF-8 crystallization. Linear Combination Analysis (LCA) suggests tetrakis(1-methylimidazole)zinc 2+ to be a suitable and stable mononuclear structure analogue for some early stage ZIF-8 intermediates. Our results pave the way for more detailed studies on physico-chemical aspects of ZIF-8 crystallization to better control tailoring ZIF-8 materials for specific applications.